(untitled) (Journal SCIENCEVOLUTION, 2025)
This hermeneutic-focused literature review analyzes the incidence of emotional intelligence as a tool to enhance academic performance and facilitate adaptation to the educational environment for both university students and educators. The objective is to examine the benefits, challenges, and opportunities in implementing emotional intelligence within higher education curricula. Academic databases such as Scopus, SciELO, Latindex, and Google Scholar were utilized to search for relevant studies. The analysis of 26 studies concludes that emotional intelligence positively influences academic performance, adaptation to the university environment, and the development of interpersonal skills among students and teaching staff. Furthermore, limitations in implementing soft skills and emotional intelligence training are identified, including insufficient professional development, low prioritization of emotional competencies in curricula, and institutional resistance to change. However, despite these challenges, emotional intelligence represents a strategic tool to strengthen educational quality and promote the integral development of pedagogical models in higher education institutions, enabling students to achieve optimal performance in their academic and professional lives.